1983
DOI: 10.1099/0022-1317-64-2-391
|View full text |Cite
|
Sign up to set email alerts
|

Defective Particles from a Persistent Baculovirus Infection in Trichoplusia ni Tissue Culture Cells

Abstract: SUMMARYAn HZ-1 baculovirus clone isolated from persistently infected Trichoplusia ni tissue culture cells was homogeneous as determined by particle morphology and restriction enzyme analysis of virus DNA. Re-establishment of a persistent infection of TN-368 cells with this clone (B1) was unsuccessful. There was a 99~o decrease in infectious virus titre following 10 passages in tissue culture at a high multiplicity of infection, and the 10th passage virus population was capable of establishing a persistently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…By culturing TN -368 cells that survived productive Hz-IV replication, Ralston et al (1981) and Burand et al (1983b) were both able to obtain cell lines persistently infected with the virus. These cell lines continued to produce infectious virus at a low level and were resistant to superinfection by Hz-IV, yet they were susceptible to infection by the heterologous virus Autagrapha califarnica NPV (AcNPV) (Ralston et al, 1981).…”
Section: Persistence Of Hz-ivmentioning
confidence: 99%
See 2 more Smart Citations
“…By culturing TN -368 cells that survived productive Hz-IV replication, Ralston et al (1981) and Burand et al (1983b) were both able to obtain cell lines persistently infected with the virus. These cell lines continued to produce infectious virus at a low level and were resistant to superinfection by Hz-IV, yet they were susceptible to infection by the heterologous virus Autagrapha califarnica NPV (AcNPV) (Ralston et al, 1981).…”
Section: Persistence Of Hz-ivmentioning
confidence: 99%
“…5) (Ralston et al, 1981). The virus is complete and infectious prior to release from infected cells, since virus recovered from cells after a brief sonication reaches a high titer sooner than virus released into the cell culture supernatant (Burand et al, 1983b).…”
Section: Replication Of Hz-iv In Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The Hz-1 virus can establish persistent and productive infections in several lepidopteran cell lines . Burand et al (1983b) showed that defective virus particles are generated following serial passage in vitro and are required for the establishment of persistent infections. The defective virus particle samples always contained a small amount of standard virus as a helper virus.…”
Section: Introductionmentioning
confidence: 99%
“…The standard Hz-1 virus particles contain a superhelical, circular, double-stranded DNA genome of 228 to 245 kb (Huang et al, 1982;Burand et al, 1983b), which is approximately twice the size reported for occluded baculoviruses (Smith & Summers, 1978) and the nonoccluded Oryctes baculovirus (Crawford et al, 1985). Based on restriction enzyme profiles and electron microscopic contour measurements of DNA molecules, the Hz-1 defective interfering (DI) particles were shown to be heterogeneous in size (Huang et al, 1982;.…”
Section: Introductionmentioning
confidence: 99%